THE CORRELATION BETWEEN PERCEPTION OF GIST STRATEGY AND STUDENTS’ WRITING DESCRIPTIVE TEXT AT MUHAMMADIYAH JUNIOR HIGH SCHOOL 1 GRESIK - Maulina, Zulya Anis (Universitas Muhammadiyah Gresik, 2017)
Writing can represent students? ability because it is covered some aspects. They are the usage of appropriate words, the usage of correct grammatical, and the usage of good marks. The problems which are faced by the students are they do not know what they are going to write and they can write but their writing is not in good organization although the teacher had explained about the generic structure of the text. Here, the researcher focuses on the GIST strategy which is used by teacher in teaching writing descriptive text. In this study, the researcher wants to know whether there is a correlation between perception of GIST strategy and students? writing descriptive text at Muhammadiyah Junior High School 1 Gresik. Besides, the researcher also want to know whether there is correlation between perception of GIST strategy and students? writing descriptive text according to the gender at Muhmmadiyah Junior High School 1 Gresik. This study uses correlation design. The researcher conducted this study in VIII A class of Muhammadiyah Junior High School 1 Gresik. There were 28 students which consist of 16 male students and 12 female students. The instruments of this study were questionnaire and students? writing test. Questionnaire were distributed to get perception of GIST strategy data and students? writing descriptive test was given to get students? writing skill data. The researcher analyzed the data by using Pearson Coefficient Correlation. Based on the results, it can be concluded that the students who have better perception of GIST strategy to be possible to have good writing descriptive text and the female students have better perception of GIST strategy than the male students. As the prove that female students have better writing in class descriptive text score than male students